Prolonged Late Mesoproterozoic to Late Triassic Tectonic Evolution of the Major Paleo-Asian Ocean in the Beishan Orogen (NW China) in the Southern Altaids - Mao, Qigui; Xiao, Wenjiao; Wang, Hao; Ao, Songjian; Windley, Brian F.; Song, Dongfang; Sang, Miao; Tan, Zhou; Li, Rui; Wang, Meng (Frontiers in Earth Science, 2022)
The accretionary processes and the continental growth of the Altaids are still controversial. The Beishan orogen situated in the southernmost Altaids and is an ideal tectonic site to address these issues. In this study we report the results of new field-based lithological mapping and structural analysis on the Huaniushan complex in the Beishan, which is composed of blocks of serpentinized ultramafic, gabbro, basalt, chert, limestone, and other rocks within a strongly deformed and cleaved matrix of sandstone and schist. Our new zircon U-Pb date reveal that a gabbro block formed at 504 ±3 Ma. Our geochemical and isotopic data of gabbroic and basaltic blocks show they are relics of Mid-Ocean-Ridge (MORB)-type and Ocean-Island-Basalt (OIB)-type oceanic lithosphere, with high values of εNd(t) (+4.3 to +14.5) and εHf(t) (+8.07 to +17.74). The maximum depositional ages (MDAs) of two sandstone blocks were dated at 309  8 Ma and 501  5 Ma, respectively. U-Pb ages and Hf isotopes of detrital zircons from the matrix sandstones indicate they were derived only from the Shuangyingshan-Huaniushan arc to the north. Accordingly, the Huaniushan complex was part of the Liuyuan accretionary complex that fringed the Huaniushan arc, and therefore formed by the northward subduction of the Liuyuan Ocean. Combined with the basalt yields zircon U-Pb age of 1071±5 Ma, we concluded that the Huaniushan complex are age of 1071 Ma to 309 Ma. Furtherly, the oceanic blocks and sedimentary matrix of the Liuyuan accretionary complex have age of 1071-270 Ma and 920-234 Ma, respectively, suggesting that the Liuyuan Ocean was still opening at ca. 234 Ma. Thus, the studies reveal that the Liuyuan Ocean, a major branch of the Paleo-Asian Ocean may have experienced a prolonged tectonic history, starting in the Late Mesoproterozoic (1071 Ma) and terminating later than middle Triassic (234 Ma), with a long subduction and development of a series of seamounts and/or plateaus emplaced into the Liuyuan accretionary complex.